2008
DOI: 10.1103/physrevb.77.064419
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature behavior ofYBaCo2O5.5: Coexistence of two spin-state ordered phases

Abstract: The low temperature antiferromagnetic-antiferromagnetic phase transition in polycrystalline YBaCo 2 O 5.5 cobaltite was studied by neutron powder diffraction. On the basis of symmetry arguments in combination with Rietveld refinement, the coexistence of two phases with different type of spin-state ordering between the diamagnetic ͑t 2g 6 e g 0 , S =0͒ and paramagnetic ͑t 2g 4 e g 2 , S =2͒ sixfold coordinated Co 3+ cations was revealed below the transformation temperature, T L ϳ 195 K. One of the phases having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 15 publications
5
42
1
Order By: Relevance
“…The refined positions practically coincide with the ones determined in Ref. [21]. Oxygen concentration and atomic coordinates remain unchanged during these manipulations.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…The refined positions practically coincide with the ones determined in Ref. [21]. Oxygen concentration and atomic coordinates remain unchanged during these manipulations.…”
Section: Resultssupporting
confidence: 59%
“…A similar situation was discussed in Ref. [21], where by means of neutron diffraction studies the symmetry of two detected phases was revealed and the models of their lattices were proposed. Using these models we performed Rietveld refinement of our X-ray diffraction pattern, which gave a rather good agreement between experimental and calculated patterns (Fig.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…A third magnetic transition has been evidenced by neutron diffraction in small rare earths such as Tb and Y. 14,18,19 This third magnetic transition is apparently absent for large rare earths ͑Pr, Nd͒. 8,18,20 MIT is accompanied by a structural phase transition characterized by a strongly anisotropic evolution of cell parameters and a discontinuity of the unit-cell volume.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The oxygen content can be changed over a wide range from 5+δ = 5.0 to 5.8 [6], which changes the ground states of these materials from the charge-ordered antiferromagnetic (AFM) insulator for δ = 0 to the optimally doped band insulator for δ = 0.5, and to the heavily hole-doped metallic ferromagnetic state for δ > 0.7. The particular doping level δ = 0.5 is associated with an oxygen vacancy ordering, which manifests itself as alternating planes of CoO 6 octahedra and CoO 5 square pyramids along the a-axis of the crystal structure, each containing one While there are several studies of the RBaCo 2 O 5+δ compounds with variable oxygen contents causing conversion of the CoO 5 pyramids to CoO 6 octahedra for δ > 0.5 (or vice versa for δ < 0.5), the information about the cation substitutions in these materials with controlled oxygen content is scarce.…”
Section: Introductionmentioning
confidence: 99%